The Darwinian tradition in context : research programs in evolutionary biology - Delisle, Richard G. (Springer, 2017)
It is the main goal of this volume to put in context the Darwinian tradition by raising questions such as: How should it be defined? Did it interacted with other research programs? Where there any research programs whose developments were largely conducted independently of the Darwinian tradition? Contributors to this volume explicitly reflect upon the nature of the relationship between the Darwinian tradition and other research programs running in parallel. In the wake of the Synthetic Theory of Evolution which was constituted in the 1930s, 1940s, and 1950s, historians and philosophers of biology have devoted considerable attention to the Darwinian tradition, i.e., linking Charles Darwin to mid-Twentieth-Century developments in evolutionary biology. Since then, more recent developments in evolutionary biology challenged, in part only or entirely, the heritage of the Darwinian tradition. Expectedly, this was followed by a historiographical "recalibration" by historians and philosophers towards other research programs and traditions part of evolutionary biology since Darwin's time. In order to acknowledge this shift, papers have been arranged along two main threads: Part I: The view that sees Darwinism as either originally pluralistic or acquiring such a pluralism through modifications and borrowings over time. Part II: The view blurring the boundaries between non-darwinian and darwinian traditions, either by holding that Darwinism itself was never quite as darwinian as previously thought, or that non-darwinian traditions took on board some darwinian components, when not fertilizing Darwinism directly. Between a Darwinism reaching out to other research programs and non-darwinian programs reaching out to Darwinism, the least that can be said is that this criss-crossing of intellectual threads blurs the historiographical field. This volume aims to open new thinking avenues about the development of evolutionary biology.
Keywords: Evolution (Biology) -- Research -- History.; Evolution (Biology) -- Philosophy -- History.; Evolutionary developmental biology -- History.; Evolution (Biology) -- History.; elektronické knihy; electronic books